An online NP-HPLC-DPPH method for the determination of the antioxidant activity of condensed polyphenols in cocoa. (November 2016) - Pedan, Vasilisa; Fischer, Norbert; Rohn, Sascha
Abstract: Unroasted cocoa beans are rich in monomeric flavanols and particularly epicatechin-based proanthocyanidin oligomers, with the latter making up to 60% of the total polyphenol content. Although the antioxidant activity of cocoa polyphenols is well known, it is still a challenging analytical field, especially, when it comes to the determination of condensed polyphenols and the evaluation of their single contribution to the overall activity. Therefore, an online NP-HPLC-DPPH assay was developed to separate the homologous series of condensed polyphenols for assessing their antioxidant capacity in relation to their degree of polymerization (DP), simultaneously. In this context, normal-phase chromatography allows separation of polyphenols based on their degree of polymerization. This study showed that an unroasted cocoa extract contains condensed polyphenols with a DP of up to 10 monomer units. By means of the online post-column derivatisation with 2, 2-diphenyl-1-picrylhydrazyl (DPPH), the antioxidant capacity of the separated condensed polyphenols was assessed. It could be shown that, with the exception of the dimers, the contribution to the total antioxidant activity decreased from monomers to decamers. However, from the single proanthocyanidins identified, nonameric and decameric proanthocyanidins were found to have the highest values for the antioxidant capacity. The degree of polymerization associated with each molecular weight fraction was further confirmed using electrospray ionization mass spectrometry coupled with reverse-phase liquid chromatography. The online NP-HPLC-DPPH method can be used as qualitative and quantitative analysis of condensed proanthocyanidins and the simultaneous elucidation of the biological activity of proanthocyanidins in complex mixtures. Highlights: An online NP-HPLC-DPPH assay was used to separate condensed cocoa polyphenols. Correlation of antioxidant activity and degree of polymerization has been assessed. Unroasted cocoa extract contains condensed polyphenols with a DP of up to decamer. The highest value antioxidant capacity was found for nonamers and decamers.